Penentuan Rute Jakarta-Bandung pada Kendaraan Nebengers dengan menggunakan Vehicle Routing Problems with Profits - Anwar, Fahri; Baharuddin, Siti Ruqaiyah; Aulia, Dira (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
Traffic congestion in Indonesia, particularly on the Jakarta–Bandung route, significantly reduces mobility efficiency. Nebengers, a carpooling platform, offers an alternative solution to reduce private vehicle usage, but the drivers’ routes must be optimized to minimize travel costs. This study is a case study using the Vehicle Routing Problem with Profits (VRPP), the Prize Collecting Travelling Salesman Problem (PCTSP) model, and the heuristic nearest neighbor algorithm to determine the optimal route. The data considered include toll fees, fuel consumption, revenue from each drop-off point, and penalties for unvisited points. The results indicate that visiting all points produces a total cost of IDR 222,219, which is lower than the route with penalties (IDR 225,333). It is concluded that visiting all drop-off points is the best option to maximize profit and travel efficiency.